THE DEVELOPMENT STRATEGY OF LAKE KELIMUTU TOURIST ATTRACTION IN ENDE REGENCY - Selfiyah Karimah; H Hastuti (Department of Geography Education, University of Jember, 2019)
The purpose of this study is to analyze the potential and the development of Lake Kelimutu tourist attraction in Ende Regency. The data were collected through observation, documentation, and interviews with stakeholders, such as the Kelimutu National Park Office, Government Tourism Office, Community, and Visitors. The data was then analyzed descriptively for later determined of its development strategies using SWOT. The results of the study showed that the potential of Lake Kelimutu tourist attraction, besides the uniqueness of the three crater lakes, is also a diversity of flora and fauna, and it was concluded that the appropriate alternative strategy for developing Lake Kelimutu tourist attraction was the S-O strategy (strength and opportunity), they are: creating an integrated tourist package marketing strategy for natural and cultural tourism, using various existing social media to promote the uniqueness of the ever-changing colors of the lake, working with various travel agents to provide special discounts or special services for tourists, and creating special transport routes to Lake Kelimutu from Ende. Keywords: potential, development strategy, tourist site, Lake Kelimutu. References Bunghez, C.L. (2016). The Importance of Tourism to a Destination’s Economy. Journal of Eastern Europe Research in Business & Economics, 1-9. Damanik & Weber. (2006). Perencanaan Pariwisata: Dari Teori ke Aplikasi. Yogyakarta: Andi. Engelhard. (2005). Culturally and Ecologically Sustainable Tourism Development through Local Community Management. Culture and Sustainable Development in the Pacific: ANU Press. Fandeli, C. (2002). Perencanaan Kepariwisataan Alam. Yogyakarta: Fakultas Kehutanan Universitas Gadjah Mada. Gaol, H.L. (2014). Potensi Pariwisata Danau Tiga Warna Gunung Kelimutu dan Usaha Kerajinan Kain Tenun Lio Sebagai Atraksi Wisata. JDP, 1(1),31-50. Ismayanti. (2010). Pengantar Pariwisata. Jakarta: PT Gramedia Widisarana Indonesia. Kruja, A. (2012). The Impact of Tourism Sector Development in the Albanian Economy. Economia Seria Management, 15(1), 204-218. Marpaung, H. (2000). Pengetahuan Kepariwisataan. Bandung: Alfabeta. Mohammed, Guellil, Moestefa, Belmokaddem, Mohammed, Sahraoui.(2015). Tourism Spending-Economic Growth Causality in 49 Countries: A Dynamic Panel Data Approach. 2nd Global Conference on Business, Economic, Management and Tourism, 1613-1623. Moleong, J.L. (2007). Metodologi Penelitian Kualitatif (Rev. ed.). Bandung: Remaja Rosdakarya. Pendit, S.N. (1999). Ilmu Pariwisata Sebuah Pengantar Perdana. Jakarta: PT. Pradnya Paramita. Pitana, I Gede & Diarta, I Ketut Surya (2008). Pariwisata sebagai Disiplin Ilmu yang Mandiri. Badan Pengembangan Sumber Daya, Departemen Kebudayaan dan Pariwisata. Rangkuti, F. (2008). Teknik Mengukur dan Strategi Meningkatkan Kepuasan Pelanggan. Jakarta: PT Gramedia Pustaka Utama. Soekadijo. (2000). Anatomi Pariwisata. Jakarta: PT Gramedia Pustaka Utama. Sugiyono. (2013). Metode Penelitian Kombinasi (Mixed Methods). Bandung: Alfabeta. Sukmadinata. (2008). Metode Penelitian Pendidikan. Bandung: Remaja Rosdakarya. Tabash, M.I. (2017). The Role of Tourism Sector in Economic Growth: An Empirical Evidence from Palestine. International Journal of Economic and Financial Issues, 7(2), 103-108. Weiler, B.,& Hall, M.C. (1992). Special Interest Tourism.New York& Toronto: Halsted Press. Yoeti, O.A. (2008). Ekonomi Pariwisata: Introduksi, Informasi, dan Aplikasi.Jakarta: Kompas. Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License